Venom-Derived Peptide Modulators of Cation-Selective Channels: Friend, Foe or Frenemy - Bajaj, Saumya; Han, Jingyao (Frontiers in Pharmacology, 2019)
Ion channels play a key role in our body to regulate homeostasis and conduct electrical signals. With the help of advances in structural biology, as well as the discovery of numerous channel modulators derived from animal toxins, we are moving towards a better understanding of the function and mode of action of ion channels. Their ubiquitous tissue distribution and the physiological relevancies of their opening and closing suggest that cation channels are particularly attractive drug targets, and years of research has revealed a variety of natural toxins that bind to these channels and alter their function. In this review, we provide an introductory overview of the major cation ion channels: potassium channels, sodium channels and calcium channels, describe their venom-derived peptide modulators , and how these peptides provide great research and therapeutic value to both basic and translational medical research.